Plant Growth Promotion and Amelioration of Salinity Stress in Crop Plants by a Salt-Tolerant Bacterium - Arka Pratim Chakraborty1, Pannalal Dey2; Bishwanath Chakraborty2, Usha Chakraborty1*, Swarnendu Roy1 (Recent Research in Science and Technology, 2011)
Out of a large number of bacteria isolated from the rhizosphere of Cynodon dactylon, a facultative halophyte, nine were found to be highly salt-tolerant, growing in nutrient agar medium supplemented with 10% NaCl. Morphological, biochemical, and molecular characterization of all the isolates was done. RAPD analysis to determine relatedness among the nine bacteria were carried out, which revealed that all nine isolates could be grouped into 2 main clusters. In order to determine whether the isolates possess plant growth promoting activities, in vitro tests were done initially.Ã‚Â Based on the in vitro tests the isolate Ã¢â‚¬ËœS4Ã¢â‚¬â„¢ was selected as a potential salt-tolerant PGPR. This bacterium was identified as Bacillus cereus. For in vivo tests, this bacterium was applied as an aqueous suspension to the rhizosphere of 3 plants- Vigna radiata, Cicer arietinum and Oryza sativa; a set of each plant was also applied with 200mM NaCl solution 3 times a week after 15 days of growth.Ã‚Â Results revealed that the bacterium could promote growth of the seedlings significantly which showed increased height, number and length of leaves, as well as root and shoot biomass. The ability of the bacterium to solubilize soil phosphate was also confirmed. B.cereus could also elicit antioxidant responses against salt stress in the plants, as evidenced by increased activities of enzymes such as superoxide dismutase, peroxidase, ascorbate peroxidase and catalase. Besides, it could also induce the activities of defense enzymes such as chitinase, ÃŽÂ²-1, 3 glucanse and phenyl alanine ammonia lyase associated with induced systemic resistance. Results imply that the bacterium acts through a combination of direct and indirect mechanisms.